1972
DOI: 10.1016/s0006-3495(72)86154-x
|View full text |Cite
|
Sign up to set email alerts
|

DNA Chain Elongation and Joining in Normal Human and Xeroderma Pigmentosum Cells after Ultraviolet Irradiation

Abstract: DNA synthesized in human cells after ultraviolet (UV) irradiation is made in segments of lower molecular weight than in unirradiated cells. Within several hours after irradiation these smaller units are both elongated and joined together. This repair process has been observed in normal human fibroblasts, HeLa cells, and fibroblasts derived from three types of xeroderma pigmentosum patients-uncomplicated with respect to neurological problems, complicated (de Sanctis-Cacchione syndrome), and one with the clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
23
0

Year Published

1973
1973
2005
2005

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…It is evident that the endonuclease is specific for U .V .-damaged DNA . In addition, by comparison with previous reports for inter-dimer distance (Buhl, Stillman, Setlow and Regan 1972, Lehmann 1972, Clarkson and Hewitt 1976, this endonuclease is also specific for dimers . A clear dose response is evident, and this is independent of the amount of endonuclease used .…”
supporting
confidence: 75%
“…It is evident that the endonuclease is specific for U .V .-damaged DNA . In addition, by comparison with previous reports for inter-dimer distance (Buhl, Stillman, Setlow and Regan 1972, Lehmann 1972, Clarkson and Hewitt 1976, this endonuclease is also specific for dimers . A clear dose response is evident, and this is independent of the amount of endonuclease used .…”
supporting
confidence: 75%
“…Buhl et al showed that in one XP variant cell line (XP4BE), after UV-irradiation low molecular weight newly synthesized DNA was converted into high-molecular-weight DNA after 8 hr (23). Our more detailed kinetic study has revealed that this process was much slower in cultured fibroblasts from three (Figs.…”
Section: Resultsmentioning
confidence: 67%
“…16). As in bacteria (17), newly synthesized DNA in UV-irradiated mammalian cells is smaller than in unirradiated cells, but on prolonged incubation it eventually attains a high molecular weight similar to that from unirradiated cells (18)(19)(20)(21)(22)(23). The interpretation attributed to these observations is that DI4A synthesis is temporarily delayed by a pyrimidine dimer, and then continues beyond the ditner, leaving a gap that is subsequettly sealed.…”
mentioning
confidence: 97%
“…The existence of the latter process has been known for Ͼ30 years from studies in excision repair-deficient strains of the molecular size of DNA synthesized at various times after UV irradiation; although DNA synthesized soon after irradiation is of smaller size than its counterpart from unirradiated cells, indicating the presence of gaps and interruptions, its size corresponds to that of control DNA when isolated from the irradiated cells after a period of incubation, showing that the gaps have been filled and interruptions sealed (1). Although initially discovered in Escherichia coli (1), similar results have also been found in other organisms, including mammalian cells (2)(3)(4) and budding yeast, Saccharomyces cerevisiae (5,6). Even though the phenomena are similar, however, different mechanisms appear to be used in E. coli and the eukaryotes.…”
mentioning
confidence: 55%